Reason Liberated. "Golem XIV" as an Example of Singularity - Owczarek, Karolina (Hybris, 2019)
One of the most important transhumanistic ideas is singularity which can be described as a horizon of events, prediction horizon, transitional phase or emergence of conscious artificial intelligence. So nowadays it has different references. This article is an attempt to illustrate singularity based on Stanisław Lem’s novel and philosophical essay Golem XIV. This novel shows how the evolution of AI from ordinary computer to artificial conscious superintelligence could look like. It is also an illustration of possible relations between human and non- human intelligence. Lem appears here as philosopher and visionary who tries to think about the future, when human creates a being more perfect than himself. He is far from vision of omnipotence of computers.